Doubling agricultural growth in Uttar Pradesh: Sources and drivers of agricultural growth and policy lessons - Smriti Verma; Ashok Gulati; Siraj Hussain (Indian Council for Research on International Economic Relations (ICRIER), 2017)
Landslide victory of the Bharatiya Janata Party in state assembly elections of Uttar Pradesh in March 2017 offers a golden opportunity to change the face of UP's agriculture and thus the fate of millions that depend on it. UP with a population of more than 220 million is the most populous state of India. As per Census 2011, 59 percent of its workforce was engaged in agriculture; average holding size was just 0.76 ha with 92 percent of holdings being small and marginal; and 29 percent of its population was below the poverty line in 2011-12. As per the Situation Assessment Survey of NSS (2012-13), average monthly income of an agri-household in UP was the third lowest in the country. UP's agri-GSDP grew at 2.5 percent per annum over the period FY2001 to FY2015. The research in this paper about sources and drivers of agri-growth in UP indicates that UP has the potential to double its agri-growth from 2.5 percent to 5 percent per annum. This can be achieved if the UP government focuses on erecting a robust procurement system of wheat and paddy ensuring the Minimum Support Price to farmers; propelling the dairy sector by raising milk processing levels from about 12 to at least 30 percent over the next five years; rationalizing sugarcane pricing based on the Rangarajan Committee (2012) formula and freeing up molasses from all reservations; and finally introducing innovative farming practices and technologies in cultivation of fruits and vegetables. These policies can be backed by infrastructural investments in rural roads, power supply to rural areas, and improved irrigation, especially in the Bundelkhand region. If the new regime in UP puts this package of policy reforms on priority, it can fulfill the Prime Minister's vision of "sabka saath, sabka vikas" and also reap rich political and economic dividends through faster poverty alleviation and development for all, making UP truly an "Uttam Pradesh".
Keywords: Q10; Q18; 330; Uttar Pradesh agriculture; agricultural growth; "sabka saath; sabka vikas"